Air Pollution during Pregnancy and Birth Outcomes in Italy - Alessandro Palma; Inna Petrunyk; Daniela Vuri (Institute of Labor Economics (IZA), 2019)
We investigate the impact of fetal exposure to air pollution on health outcomes at birth in Italy in the 2000s combining information on mother's residential location from birth certificates with information on PM10 concentrations from air quality monitors. The potential endogeneity deriving from differential pollution exposure is addressed by exploiting as-good-as-random variation in rainfall shocks as an instrumental variable for air pollution concentrations. Our results show that both average levels of PM10 and days above the hazard limit have detrimental effects on birth weight, duration of gestation as well as overall health status at birth. These effects are mainly driven by pollution exposure during the third trimester of pregnancy and further differ in size with respect to the maternal socio-economic status, suggesting that babies born to socially disadvantaged mothers are more vulnerable. Given the non negligible effects of pollution on birth outcomes, further policy efforts are needed to fully protect fetuses from the adverse effects of air pollution and to mitigate the environmental inequality of health at birth.
Keywords: I18; J13; Q53; Q58; 330; air pollution; particulate matter; birth weight; pre-term birth; environmental policies